Occupational stressor and job performance among employees of oil and gas companies - Mazaitul Akma, Jalil (2019)
The purpose of this study is to identify the relationship between work overload, job stress, role ambiguity and self-efficiency to occupational stressor and job performance. The survey method was used to collect the primary data through the use of a questionnaire to the employee oil and gas. The total 250 of questionnaire were distributed and all 152 questionnaires were successfully collected. The descriptive and inferential analyses were conducted. The results of this study showed work overload, job stress, role ambiguity and self-efficiency to occupational stressor and job performance are all positive correlated occupational stressor and job performance. This results of this study provides information about job stress among employee oil and gas in the policy maker for improvement the oil and gas company.